Redistributive policies in general equilibrium - Georgios Oikonomides; Apostoles Philippopulos; Stylianos Sakkas (European Commission, Joint Research Centre (JRC), 2021)
We develop a general equilibrium OLG model to evaluate a wide menu of popular redistributive policies in a unified context. We work in two steps: First, we study how initial conditions in human and financial capital, as inherited from family background, shape individuals' human capital, and hence their work opportunities, income and wealth, and eventually macroeconomic outcomes. Second, we study which policies can reduce this type of inequality without, hopefully, damaging macroeconomic efficiency.
Keywords: D63; H21; H50; 330; Inequality; efficiency; government expenditures; public policy